Retreatment of Chronic Hepatitis C Infection: Real-World Regimens and Outcomes From National Treatment Programs in Three Low- and Middle-Income Countries. (3rd July 2021) - Boeke, Caroline E; Hiebert, Lindsey; Waked, Imam; Tsertsvadze, Tengiz; Sharvadze, Lali; Butsashvili, Maia; Zakalashvili, Mamuka; Naing, Win; Gupta, Neil; Kateera, Fredrick; McClure, Craig; Ward, John W; et al.
Abstract: Access to recommended second-line treatments is limited for patients who fail initial hepatitis C virus (HCV) therapy in low- and middle-income countries. Alternative regimens and associated outcomes are not well understood. Through a pooled analysis of national program data in Egypt, Georgia, and Myanmar, we observed SVR rates >90% for alternative retreatment regimens.